Level of adoption in recommended buffalo husbandry practices in Uttar Pradesh - Sachan, Ranjana; Sankhala, Gopal; Roy, Rakesh; Manjusha, Jyoti (Indian Journal of Dairy Science, 2016)
The present study was carried out in Unnao district of Uttar Pradesh among 120 dairy farmers to measure the level of adoption in recommended buffalo husbandry practices. The study shows that majority of the respondents had medium level of adoption in breeding, feeding, management, clean milk production and health care practices recommended for buffalo husbandry practices. Mean adoption level in breeding, management, clean milk production and health care practices was medium whereas feeding was slightly high. The study also reveals that that the extent of adoption of the respondents in the overall adoption in buffalo husbandry practices was 51.96 percent wherein it highest for breeding practices and lowest in healthcare practices. The study further reveals that rate of adoption was highest in large farmers and lowest in landless farmers.